Dari Konflik ke Kolaborasi: Pelatihan Win-Win Solution bagi Siswa SMAK BPK 2 Bandung - Candra Sinuraya; Meily Margaretha; Susanti Saragih (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This community service program aimed to improve students’ conflict management skills through a win-win solution approach at SMAK BPK 2 Bandung. Conflict among adolescents frequently occurs due to miscommunication, differences in opinions, emotional reactions, and group assignment problems. Therefore, students need communication and emotional regulation skills to manage interpersonal conflicts constructively. The training involved 26 students and was conducted through interactive activities, including ice breaking, conflict simulations, group discussions, self-reflection, and collaborative problem-solving exercises. Evaluation was carried out using pre-test and post-test instruments, reflective paperwork, and participant observation. The results showed an increase in students’ understanding and skills related to conflict management. The average pre-test score increased from 3.97 to 4.37 in the post-test, while the usefulness evaluation reached an average score of 4.65 out of 5. Students demonstrated improved emotional control, communication skills, empathy, and the ability to seek mutually beneficial solutions. The findings indicate that experiential learning combined with a win-win solution approach effectively enhances students’ interpersonal conflict resolution skills. This program can serve as an alternative model for character education and social-emotional learning activities in schools.